Tradycja czy nowoczesność – obraz współczesnego ojca dziecka w wieku wczesnoszkolnym. Raport z badań - Łucja Reczek-Zymróz (Problemy Wczesnej Edukacji)
Family faces new challenges – a father does not have to maintain his family or gain and defend. The emotional contact is becoming the foundation. In the text of this article, the changes which were the consequence of the father’s functioning were analysed: the model of a family, activities considered typical for fathers and mothers, caring and pedagogical activities undertaken by respondents. In the research carried out by means of a questionnaire (interview), 200 fathers (aged 30–50) of early school-age children participated. The research was done in Poland between 2018 and 2020. The results of the research indicate that the role of the father is changing, although often declaratively. In families, the focus of child care has shifted towards the father, and its main task is no longer to support the family materially. Undoubtedly, these changes determine the education of respondents, as well as – to a lesser extent – the age of fathers.